CELIE’S ENDEAVORS AS THE LIBERAL FEMINISM SYMBOL IN ALICE WALKER’S THE COLOR PURPLE - laksmi diana (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Abstract Liberal Feminism has been one of highly discussed theme in literature works, especially novels. One the novels was Alice Walker’s The Color Purple. This article discusses the main character’s struggles to get free from abuse and oppression she experienced as a wife and a stepdaughter. Her reconciliation with her abusive husband in the end of the story was believed as a symbol of the success of liberal feminism movement.